Yield Performances and Cup Quality of Some BTRI Test Clones of Tea - Hossain, MI; Dutta, MJ; Khan, AQ; Mamun, MSA; Rana, MM (International Journal of Agricultural Research, Innovation and Technology, 2013)
A long term experiment was conducted to investigate the yield and quality performances of four vegetative propagated test clones of tea coded as A/8/01, A/17/22, A/22/27 and A/22/40 at Bangladesh Tea Research Institute (BTRI) farm during 1996-2010. A standard clone BT1 was considered as control. Cuttings of the test clones were collected from the selected bushes of Amo tea estates and were raised at BTRI nursery. Then saplings were put to long term yield and quality trial following Latin Square Design (LSD) with 3 replications. The green leaf was harvested at weekly interval during the plucking season starting from mid March to mid December throughout the experimental period. Yield data were recorded and analyzed statistically using MSTAT programme. Results of the experiment revealed that among the test clones A/22/40 gave the highest significant yield of 3509.1 kg ha-1 of made tea followed by BT1 (3203.69 kg ha-1), A/8/01 (2912.24 kg ha-1), A/17/22 (2817.76 kg ha-1) and A/22/27 (2278.78 kg ha-1) from the average of 9 years (2002-2010) at mature stage. At immature stage i.e. 1st year to 5th year after plantation yield difference was insignificant. The overall cup quality of the test clones was assessed by conventional organoleptic test. The cup quality of A/8/01, A/17/22, A/22/40 as well as the standard clone BT1 was found to be above average (AA) while the cup quality of A/22/27 was average (A). Considering the yield and quality potentials, the test clone A/22/40 has appeared quite promising to be released as a standard clone. DOI: http://dx.doi.org/10.3329/ijarit.v1i1-2.13925 Int. J. Agril. Res. Innov. & Tech. 1 (1&2): 24-28, December, 2011